Case study of forestry certification and CdeC`s sofware validation for forestry management and the chain of custody of a forestry company in Petén, Guatemala - Morales Cancino, J.C. (2005)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2005